Physical organization of the Bradyrhizobium japonicum nitrogenase gene region. - Adams, T H (1984)
In Bradyrhizobium japonicum USDA 110 the three genes that encode the nitrogenase enzyme complex are separated into two transcription units, nifH and nifDK. We have physically mapped a 33-kilobase-pair region of the B. japonicum genome that contains both nifH and nifDK. The nifDK operon is located transcriptionally upstream from nifH, and all three genes are transcribed in the same direction. Within the 20-kilobase-pair region that separates the promoters for these two transcription units, we have identified a region homologous to the Klebsiella pneumoniae nifA gene. This nifA homology is situated about 6 kilobase pairs upstream from the nifH transcriptional initiation signal, in an analogous position to the nifA-like locus previously described for Rhizobium meliloti. In addition, we have characterized a second distinct nifA homology in B. japonicum that is not directly linked to the nitrogenase structural gene region.